Exploring Client Adherence Factors Related to Clinical Outcomes. Issue 3 (August 2014) - Gill, Liz; Cassia, Fabio; Cameron, Ian D.; Kurrle, Susan; Lord, Stephen; Fairhall, Nicola; Lockwood, Keri; Langron, Colleen
With the increase in chronic disease and the ageing of the population, understanding requisite self-management adherence of people who are frail is important, especially given its association with service outcomes. This study sought to investigate five key client adherence factors reported in the literature, and frailty reduction in a clinical trial intervention group. The intervention participants in the Frailty Trial were stratified into three groups on the basis of their frailty score; improved, unchanged or deteriorated, and a sample meeting the inclusion criteria was randomly selected from each group. The intervention therapists were asked to complete a survey for each of the clients seeking their views on client motivation, client participation, client–therapist relationship, client trust and the value of the service to the client. A strong relationship was demonstrated between each of the five adherence variables and the outcome of the service, with motivation and participation having the greatest impact.